If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/2(6x+4)=3x+4
We move all terms to the left:
1/2(6x+4)-(3x+4)=0
Domain of the equation: 2(6x+4)!=0We get rid of parentheses
x∈R
1/2(6x+4)-3x-4=0
We multiply all the terms by the denominator
-3x*2(6x+4)-4*2(6x+4)+1=0
Wy multiply elements
-6x^2(6-8x(6+1=0
| F(x+1)=4x^2+5x-3 | | 3^{2x-1}=3^{x+2} | | 3x-10=-2+6x | | 6(2x-7)=12x+5 | | 2x+35+3x=90 | | 3x-1+4x+5=32 | | 0.5=4.1x-2(1.3+4) | | 4x-8=-x+12 | | 6+9x+8x+9x+8x+17-9x+8x-2+19-7x= | | 6x-7+10=3x-9 | | 8.2^x=64.5 | | y-19=42 | | 8+19=-3(8x-9) | | -4.8=1.5g | | -5(4-x)x=-5x+20 | | 4x-12x+9=6x-19 | | 5x-9=78+2x+10 | | r4−5=−2r−7≤3. | | 12+2x+1=5x | | c+8=-2 | | 30y(y-10)=15y | | 2.6b=13 | | 3{b+6}=27 | | 4(x-1=5(x-2) | | 12t+10t+14=80 | | 25/x=8/1 | | -5(8x-4)-7x=-19-8x | | 7x-2x+x=48 | | 7(n-8)=-84 | | 3y-11=161 | | 2(y+1)+3(y-2)=5y+1 | | 198=-7(1+7x)+8x |